The Role of Deliberative Collaborative Governance in Achieving Sustainable Cities - Gollagher, Margaret; Hartz-Karp, Janette (Adver, SUSTDE, 2013)
Sustainability issues involve complex interactions between social, economic, and environmental factors that are often viewed quite differently by disparate stakeholder groups. Issues of non-sustainability are wicked problems that have many, often obscure causes, and for which there is no single, straightforward solution. Furthermore, the concept of sustainability is itself contested. For example there are disputes over whether a strong or weak interpretation of sustainability should be adopted. In cities, as elsewhere, sustainability therefore requires discursive plurality and multiple sites of action. It is the thesis of this paper that effective problem solving, decision-making and enacting of a sustainability agenda require deliberative collaborative governance (DCG), a logical hybrid of the closely related fields of deliberative democracy and collaborative governance. We provide a provisional typology of different modes of deliberative collaborative governance, explaining each with a sustainability example, with a particular focus on DCG initiatives for planning in Western Australia. It is argued that the lens provided by such a typology can help us to understand the factors likely to promote better resolution of wicked problems and increased sustainability.